CONTROL OF BACTERIOSES IN CULTURE OF MELON - Garcés Fiallos, Felipe Rafael (2009)
Among the bacterial born diseases there are several that affect melon crop worldwide, being the bacterial spot of the fruits or aqueous stain, caused by Acidovorax avenae subsp. citrulli the most important. The losses may reach 100% damage when environmental conditions are ideal for the development of the pathogen. The symptoms of this disease are easily observed in the fruits and there is not a well established measure for their control yet. Despite that the most relevant and important information available and related to this fitobacteria, including the control measures more used in the melon production are reviewed.